The Neural Foundations of Creativity in the Default Mode Network - Jo, Sooyoung (Technium Social Sciences Journal, 2021)
Network neuroscience research is providing increasing specificity on the contribution of large-scale brain networks to creative cognition. This study reviews several neural processes that underlie creativity by examining the functional connectivity of multiple brain regions as identified by functional magnetic resonance imaging (fMRI) scanning, often utilizing divergent thinking tasks. Many of these processes will be based primarily in the interaction between the default mode and executive control networks and will closely parallel cooperation between controlled and spontaneous cognition. This paper will also review two other neural mechanisms, one of which links creativity to the Big Five Personality Factor Openness to experience and the second will involve the salience network.